APPROXIMATING SOLUTIONS OF NONLINEAR HYBRID CAPUTO FRACTIONAL INTEGRO-DIFFERENTIAL EQUATIONS VIA DHAGE ITERATION PRINCIPLE - Abdelouaheb Ardjouni (Ural Mathematical Journal, 2019)
In this article, we prove the existence and approximation of solutions of the initial value problems of nonlinear hybrid Caputo fractional integro-differential equations. The main tool employed here is the Dhage iteration principle in a partially ordered normed linear space. An example is also given to illustrate the main results.